The Role of Continuing Education in Improving Learning Quality Based on Netizen Responses on Social-Media - Syifa Nur Azizah; Yadi Suryadi; Neneng Jessi Asrina (CV. Ksatria Siliwangi, 2026)
Continuing education plays a crucial role in improving the quality of learning and developing superior human resources amidst increasingly rapid social and technological developments. This study aims to examine the role of continuing education in improving the quality of learning and developing superior human resources based on netizen responses on social media. This study employed a netnography method with a qualitative approach. Data were collected through observation and documentation of netizen posts and comments on social media discussing education issues, particularly public views on the importance of schools and formal education. Data sources consisted of primary data in the form of netizen responses and secondary data obtained from journals and relevant scientific articles. Data analysis was conducted using descriptive qualitative methods by categorizing and interpreting netizen responses according to the research focus. The results indicate that the majority of netizens have a positive view of continuing education and view it as a long-term process that plays a role in shaping individual mindsets, character, and maturity. These findings demonstrate that continuing education contributes to improving the quality of learning and supports the formation of superior human resources. The conclusion of this study emphasizes the need for continued development and support from various parties to produce human resources with high academic and character qualities. Keywords: Continuing education, Quality, human resource development, netnography.